Deciphering microbial syntrophic mechanisms for simultaneous removal of nitrate and Cr(VI) by Mn@Corn cob immobilized bioreactor: Performance, enhancement mechanisms and community assembly. (November 2022) - Gao, Zhihong; Bai, Yihan; Su, Junfeng; Ali, Amjad; Huang, Tinglin; Zhai, Zhenyu; Wang, Yue
Graphical abstract: Highlights: Immobilized carrier served prerequisites for cellulose degradation and Mn cycling. Bioreactor achieved 96.34 and 95.37% removal efficiencies of NO3 − -N and Cr(VI). Symbiotic relationships among microorganisms were enhanced at C/N ratio of 1.0. Community assembly structure relied on the balance of metabolism and carbon supply. Different elemental cycles in the community were coupled with contaminant removal. Abstract: When bioremediation is applied to Cr(VI) and NO3 − -N contaminated groundwater, the lack of carbon sources and weak physiological activity dramatically affect the treatment efficacy. Hence, a bioreactor consisting of cellulose degradation-manganese (Mn) cycling bilayer carrier and two core strains was established. After 270 operating days, the experimental group (EG) achieved 96.34 and 95.37% of NO3 − -N and Cr(VI) removal efficiency, respectively. When the C/N ratio was reduced to 1.0, cellulose-degrading strain CDZ9 produced significantly hydrolyzed cellulose from the corn cob substrate. Meanwhile, the balance between microbial metabolic activity and carbon supply was manipulated by the dissimilatory Mn-reducing strain MFG10. Dissolved organic matter response in EG provided evidence for enhanced carbon utilization and electron transfer processes. The syntrophic relationship between EG core strains significantly enhanced bioreactor metabolism and bioactivity. It drove the coupling of different elemental cycles with contaminant removal including carbon metabolism, nitrogen metabolism, Mn cycle and Cr(VI) reduction.